2021
DOI: 10.1371/journal.pntd.0009336
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of anti-Zika virus IgM, IgAM and IgG ELISAs during co-circulation of Zika, dengue, and chikungunya viruses in Brazil and Venezuela

Abstract: Background Serological diagnosis of Zika virus (ZIKV) infection is challenging because of the antibody cross-reactivity among flaviviruses. At the same time, the role of Nucleic Acid Testing (NAT) is limited by the low proportion of symptomatic infections and the low average viral load. Here, we compared the diagnostic performance of commercially available IgM, IgAM, and IgG ELISAs in sequential samples during the ZIKV and chikungunya (CHIKV) epidemics and co-circulation of dengue virus (DENV) in Brazil and Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 64 publications
(107 reference statements)
2
12
0
Order By: Relevance
“…Immunoassay for nonstructural protein 1 can be used as an alternate test for dengue virus infection. IgM for the flaviviruses particularly dengue, Zika, and chikungunya may cross-react causing diagnostic uncertainties [ 7 ]. Plaque reduction neutralization tests (PRNTs) with > fourfold higher titers can sometimes be used for confirmation.…”
Section: Spectrum Of Neurological Clinical Disorders Associated With ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoassay for nonstructural protein 1 can be used as an alternate test for dengue virus infection. IgM for the flaviviruses particularly dengue, Zika, and chikungunya may cross-react causing diagnostic uncertainties [ 7 ]. Plaque reduction neutralization tests (PRNTs) with > fourfold higher titers can sometimes be used for confirmation.…”
Section: Spectrum Of Neurological Clinical Disorders Associated With ...mentioning
confidence: 99%
“…These can impact the nervous system at any level and lead to a variety of syndromes such as autoimmune encephalitis, acute demyelinating encephalomyelitis (ADEM), acute inflammatory demyelinating polyradiculopathy (AIDP), and its variants [ 6 ]. Antibody cross-reactivity across different arboviruses, particularly flaviviruses, may pose challenges for serological diagnosis and serosurveys to assess prevalence or emergence of arboviruses [ 7 12 ]. Further advances in accurate point-of-care diagnostics will help not only with patient care but also surveillance of various co-circulating arboviruses in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have utilized Euroimmun and have reported Zika specificity >90% [ 21 , 22 ], although the test subjects often included small groups of infected travelers who resided outside flavivirus-endemic countries. More recently, however, the accuracy of these commercial tests has been brought into question by studies in flavivirus-endemic regions, including Salvador (Brazil) [ 23 ], Rio de Janerio (Brazil) [ 24 ], and Carabobo (Venezuela) [ 25 ]. Studies have revealed that IgM ELISAs have adequate specificity, yet poor sensitivity for capturing active ZIKV infections.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have described homemade protocols that achieve better parameters than commercial tests [ 22 ] and rapid antigen-detection assays [ 24 ]. The vast majority of studies have focused on the diagnosis of dengue, evaluating cross-reactivity with ZIKV, which is especially important for serological discrimination in endemic regions with co-circulation of these viruses [ 25 ]. Therefore, many rapid DENV NS1 detection tests have been developed [ 26 ].…”
Section: Conventional Methodologies For Direct Detection Of Flavivirusmentioning
confidence: 99%